A survey on educational data mining techniques in predicting student’s academic performance - Amutha, P; R. Priya, Dr (International Journal of Engineering and Technology, 2018)
The massive growth in the educational sector needs to create awareness about handling the huge volume of student data. The educational data mining is a technique to extract information from these volumes of data. Nowadays educational data mining technique plays a vital role in predicting academic performance. The objective of this study is to explore the extended knowledge of different educational data mining techniques, which have been used to predict the academic performance.Â Â